Місце і значення формування педагогічних умов професійної підготовки майбутніх інженерів-програмістів у технічному університеті - Гончаренко, Тетяна Євгенівна (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2013)
В статті розглядається місце педагогічних умов в структурі педагогічної науки. Аналізується поняття "умова" з різних боків – загальнонаукового, філософського, психологічного та педагогічного. Особлива увага приділяється формуванню педагогічних умов, бо вони є запорукою якісної підготовки спеціалістів з ІТ технологій.

The paper examines the place of pedagogical conditions in the structure of pedagogical science. The concept ’condition’ is examined from different sides - scientific, philosophical, psychological and pedagogical. Special attention is paid to the pedagogical conditions formation, as they are the key to a high-quality professional training of the IT specialists
The place and importance of the pedagogical conditions of future engineers’ professional training at a technical university
Keywords: закони педагогіки; закономірності; педагогічні умови; принципи навчання; навчальний процес; laws of pedagogy; regularities; pedagogical conditions; principles of learning; training process